2012
DOI: 10.1007/s11262-012-0744-7
|View full text |Cite
|
Sign up to set email alerts
|

Prion protein gene polymorphism and genetic risk evaluation for scrapie in all Turkish native sheep breeds

Abstract: The aim of this study was to identify the prion protein (PrP) gene polymorphism in a total of 1,110 healthy sheep from 18 Turkish native sheep breeds. There were nine alleles and 22 genotypes observed based on codons 136, 154, and 171 of the PrP gene. The ARQ allele was predominant for all breeds. The most resistant allele to scrapie, ARR, was present in all breeds. The VRQ allele, associated with the highest susceptibility to scrapie, was detected at low frequencies in İvesi (0.06), Kıvırcık (0.021), Sakız (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 30 publications
6
13
0
Order By: Relevance
“…While the ARR allele, related to high resistance, is present at 28%, the VRQ allele, which is the most susceptible one, is only present at 0.43%. These data are compatible with those obtained from other Turkish native sheep breeds (15,(18)(19)(20)(21). With respect to their relevance to disease resistance/ susceptibility, PrP genotypes were classified into five groups from the most resistant (R1) to the most susceptible (R5) (7), as presented in Table 1.…”
Section: Discussionsupporting
confidence: 82%
“…While the ARR allele, related to high resistance, is present at 28%, the VRQ allele, which is the most susceptible one, is only present at 0.43%. These data are compatible with those obtained from other Turkish native sheep breeds (15,(18)(19)(20)(21). With respect to their relevance to disease resistance/ susceptibility, PrP genotypes were classified into five groups from the most resistant (R1) to the most susceptible (R5) (7), as presented in Table 1.…”
Section: Discussionsupporting
confidence: 82%
“…Higher frequencies of the ARQ allele have been reported in scrapie-affected sheep (Ekateriniadou et al, 2007a). Similar frequencies of the ARQ allele were reported in Italy (Granato et al, 2013, Martemucci et al, 2015, in Brazil (Ianella et al, 2012) and in Turkey (Meydan et al, 2012), whereas higher frequencies (74-86%) were observed in Awassi and Assaf sheep populations (Gootwine et al,2008).…”
Section: Discussionsupporting
confidence: 72%
“…This genotype is detected for the first time in Greece. Till now, it has been reported in Chinese Hu sheep (0.56%, F. Guan et al, 2011), in North Western China (0.40%, Zhao et al, 2012, in Turkey (0.1%, Meydan et al, 2012) and in Italy (1.7% in Foza breed, Granato et al, 2013). The very rare genotype ARK/VRQ was found only in Chios crossbred (0.31%) and the average frequency in the study population was 0.14%.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations